2010
DOI: 10.1177/0300985810389317
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Markers for Myeloid Neoplasms

Abstract: Myeloid neoplasms include cancers associated with both rapid (acute myeloid leukemias) and gradual (myelodysplastic syndromes and myeloproliferative neoplasms) disease progression. Percentage of blast cells in marrow is used to separate acute (rapid) from chronic (gradual) and is the most consistently applied prognostic marker in veterinary medicine. However, since there is marked variation in tumor progression within groups, there is a need for more complex schemes to stratify animals into specific risk group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 111 publications
(242 reference statements)
0
9
0
Order By: Relevance
“…It has been suggested that improved cytogenetic and molecular evaluation in canine leukemia could lead to improved diagnosis, better understanding of prognosis, and potentially more advanced and directed therapeutic approaches in veterinary medicine (Juopperi et al 2011;Withrow et al 2013). Herein, we performed the first large-scale genome-wide analysis and comparative assessment of DNA copy number changes in four broad subtypes of canine leukemia, namely ALL, AML, B-CLL, and T-CLL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that improved cytogenetic and molecular evaluation in canine leukemia could lead to improved diagnosis, better understanding of prognosis, and potentially more advanced and directed therapeutic approaches in veterinary medicine (Juopperi et al 2011;Withrow et al 2013). Herein, we performed the first large-scale genome-wide analysis and comparative assessment of DNA copy number changes in four broad subtypes of canine leukemia, namely ALL, AML, B-CLL, and T-CLL.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic leukemias tend to be indolent, while acute leukemias generally have a much more aggressive course. Although considered uncommon, the true incidence of leukemia in the domestic dog is unknown and most likely underdiagnosed due to the rapid clinical course and/or nonspecific clinical signs (Juopperi et al 2011;Weiss and Wardrop 2011;Withrow et al 2013). Canine leukemia can be a devastating diagnosis, often fulminant and rapidly fatal.…”
Section: Introductionmentioning
confidence: 99%
“…The latter results from a reciprocal translocation between human chromosomes 9 and 22, designated t(9;22)(q34;q11). This aberration juxtaposes the BCR gene to the gene encoding the nonreceptor tyrosine kinase ABL, resulting in the generation of a 210‐kD chimeric BCR‐ABL fusion protein (p210) with constitutive tyrosine kinase activity. Treatment of CML with the tyrosine kinase inhibitor (TKI) imatinib mesylate (Gleevec), results in significant improvement of outcomes of CML patients (some response in 96% of CML patients in the chronic phase, complete cytogenetic response in 57% at a median time of 8.3 months) .…”
Section: Discussionmentioning
confidence: 99%
“…In animals, AML has been distinguished from other myeloid neoplasias by having an undifferentiated blast cell population that comprises > 30% of nucleated cells in bone marrow or blood. 1,2 The Animal Leukemia Study Group proposed that an AML be classified as erythroleukemia (M6 subtype of leukemia) if > 50% of nucleated cells in the bone marrow are erythroid and the combined number of myeloblasts and monoblasts comprise < 30% of cells in the bone marrow 1,2 ; these criteria are based on the French-American-British classification system for AML in humans. More recent World Health Organization criteria 3 for classification of AML in humans incorporate clinical and morphological information, and genetic criteria that have prognostic importance, to derive 7 major types and numerous subtypes of AML.…”
Section: Discussionmentioning
confidence: 99%